As dinâmicas socioespaciais da Exposição Feira Agropecuária Industrial e Comercial de Maringá/Paraná /Brasil - Barros, Rafaela De Angelis (2015)
Tourism as a social-spatial phenomenon brings about distinct logic of territorialisation and creates contradictions in the promotion of the touristic place. However, the possible consequences of the inadequate use space by the activity and of the city marketing broadcast to attract more visitors and investors can cause a lot of loss to the city in many different manners. Based on the segment of Tourism on Business and Events, the present paper analyzes, under the conceptual and theoretical base of Geography and Tourism, the social-spatial dynamics of the Agriculture and Stockbreeding, Industrial and Commercial Exhibition Fair of Maringá, also known as "Expoingá". To achieve the objective, the opinion of participants about the event, services and used urban infrastructure was considered. Furthermore, the patters of spatial distribution in the complex where the event takes place and its relation to its surrounding were pondered. By considering that the event's linkage with the city configures in a set of complex elements which interact with each other in a systemic way, the referential model of the touristic system recommended by Beni (2007), the System of Tourism (Sistur), was used as base. This way, from the application of the Sistur, the observation in loco and the application of questionnaires to the main agents of the activity, it can be claimed that, despite the growing flow of visitors, the infrastructure of the part and its surroundings has not been contemplated by the measures that follow the new needs brought by the increase, and it can be concluded that the city marketing of Maringá, also embodied in the event's broadcasting speech, had not been oriented by urban politics which answer to the needs of the city's inhabitants and visitors.